2019
DOI: 10.1016/j.jbiomech.2019.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a kinematically-driven discrete element model of the patellofemoral joint

Abstract: Quantifying the complex loads at the patellofemoral joint (PFJ) is vital to understanding the development of PFJ pain and osteoarthritis. Discrete element analysis (DEA) is a computationally efficient method to estimate cartilage contact stresses with potential application at the PFJ to better understand PFJ mechanics. The current study validated a DEA modeling framework driven by PFJ kinematics to predict experimentally-measured PFJ contact stress distributions. Two cadaveric knee specimens underwent quadrice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…DEA is a computationally efficient tool compared with FEA and has gained popularity for numerous clinical and personalized applications because of its computational advantages and simplicity. 1,12,21,29 DEA has been previously validated against FEA for studies on hip contact stresses and was shown to be a computationally efficient and reliable alternative. 1 In the current application, the basic element is a springresisting compressive force.…”
Section: Contact Analysismentioning
confidence: 99%
“…DEA is a computationally efficient tool compared with FEA and has gained popularity for numerous clinical and personalized applications because of its computational advantages and simplicity. 1,12,21,29 DEA has been previously validated against FEA for studies on hip contact stresses and was shown to be a computationally efficient and reliable alternative. 1 In the current application, the basic element is a springresisting compressive force.…”
Section: Contact Analysismentioning
confidence: 99%
“…FEA and DEA are refined computational models that allow the integration of subject-specific musculoskeletal parameters and experimental data, and are of great value for understanding stress distributions in complex biological structures ( Fernandez et al, 2008 ; Farrokhi et al, 2011b ; Gustafson et al, 2019 ). The researchers believe that shear stress is related to cartilage degeneration and damage, and higher shear stress in cartilage may also be the cause of damage to the exciting nociceptors present in the subchondral bone plate of the patella ( Wojtys et al, 1990 ; ( Besier et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies highlight that this method works rapidly compared to FEA, although the range of movement is limited to the sagittal plane and the articular cartilage is modeled as an isotropic linear elastic material. Similarly, discrete element analysis (DEA) has been utilized to model hip and knee joint contacts [198][199][200]. DEA demonstrated a similar contact response compared to FEA models of the hip joint [199], and similar contact pressure distributions to experimental measurements in the PFJ [198].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, discrete element analysis (DEA) has been utilized to model hip and knee joint contacts [198][199][200]. DEA demonstrated a similar contact response compared to FEA models of the hip joint [199], and similar contact pressure distributions to experimental measurements in the PFJ [198]. DEA does not require a volumetric mesh, using shell elements instead, with which elastic springs are associated, relating to the thickness of tissue (cartilage) and elastic properties (Young modulus and Poisson ratio).…”
Section: Discussionmentioning
confidence: 99%